Поняття жилого простору в контексті дослідження ранньомезолітичних культур степової України - Сминтина, О.В. (Археологія, 2002)
В статті розглянуто поняття жилого простору в контексті дослідження ранньопервісних культур. За матеріалами ранньомезолітичних пам'яток степової України виокремлено чотири таких простори. Встановлено два етапи ix освоєння та проаналізовано перспективи визначення етнічності жилого простору. В статье рассматривается понятие жилого пространства в контексте исследования раннепервобытных культур. По материалам раннемезолитических памятников степной Украины определены четыре таких пространства (Нижнее Подунавье, Днестро-Бугский регион, бассейн Днепра и бассейн Северского Донца), каждое из которых характеризуется неповторимыми чертами образа жизни и культуры жизнеобеспечения его обитателей. Выделены два этапа в освоении этих пространств (дриас ІІІ — начало пребореала; середина — вторая половина пребореала), рассмотрены перспективы установления этничности жилого пространства. The concept of living area in the context of studying the early primitive cultures is considered in the paper. Four such living areas are defined according to the materials of the Early Mesolithic sites of the steppe  Ukraine (the lower Danube area, the Dniester and Bug area, the Dnieper basin, and the Seversky Donets basin). The unique features of life and the culture of life- support of their inhabitants, characterize each of these areas. Two stages of settling these areas are singled out (Drias III — the beginning of Pre-boreal; the middle — the second half of Pre-boreal); the perspectives of reconstruction of the ethnic situation of a living area are analyzed.